The use of oil palm frond compost as additive in soilless culture system for crop production. - Bachtiar, Erwan; Ismail, Mohd Razi; Ibrahim, Ibrahim (2001)
A study was conducted to determine the use of oil palm frond compost as additive in soilless culture system and its impact on growth, physiological responses and yield of cauliflower. Coconut coir dust as medium in soilless culture improved growth and yield of cauliflower. However, the use of oil palm frond compost significantly enhanced leaf growth and other physiological responses as well as improved yield of the cauliflower. It therefore seemed oil palm frond compost can substitute better the use of peat coconut coir dust in soilless culture system.